Implementation and evaluation of a culturally grounded group-based HIV prevention programme for men who have sex with men in Ghana. Issue 7 (3rd July 2021) - Abubakari, Gamji M'Rabiu; Nelson, LaRon E.; Ogunbajo, Adedotun; Boakye, Francis; Appiah, Patrick; Odhiambo, Apondi; Sa, Ting; Zhang, Nanhua; Ngozi, Ironyah; Scott, Adjei; Maina, Geoffrey; Manu, Abubakar; et al.
ABSTRACT: This study examined the feasibility and acceptability of an evidence-based HIV prevention programme for men who have sex with men (MSM) in Ghana through a participatory approach. The programme involved 57 self-identified adult cisgender MSM and led by a community-based organisation in collaboration with local nurses. We used an explanatory mixed-method design to evaluate the programme. We computed descriptive statistics, relative frequency, and paired proportionate analysis for the survey data and subjected the focus groups data to summative content analysis. Five key themes from the qualitative data indicated strong evidence of the acceptability and efficacy of the programme among MSM. The programme contributed to building social support networks, a sense of social justice among MSM, and facilitated the development of personalised HIV prevention menus by the participants. We observed increases in HIV testing (from 4% to 17%) and increases in the relative frequency of condom use for anal, oral, and vaginal sex. The programme served as an example of a successfully implemented culturally grounded intervention that has the potential to increase HIV and STI awareness and prevention among MSM in Ghana and other highly stigmatised environments.